On‐Demand Ambient Ionization of Picoliter Samples Using Charge Pulses1. (20th April 2015) - Li, Anyin; Hollerbach, Adam; Luo, Qingjie; Cooks, R. Graham
Abstract: Relay electrospray ionization (rESI) from a capillary containing a sample solution (or from an array of such capillaries) is triggered by charge deposition onto the capillary. Suitable sources of primary ions, besides electrosprays, are plasma ion and piezoelectric discharge plasma sources. With no requirement for physical contact, high‐throughput sample screening is enabled by rapidly addressing individual secondary (sample) capillaries. Sub‐pL sample volumes can be loaded and sprayed. Polar analytes, including neurotransmitters, phosphopeptides, oligonucleotides, illicit drugs, and pharmaceutical compounds are successfully ionized by rESI with concentration sensitivities (0.1 ppb for acetylcholine) which are similar to nanoESI but absolute sensitivities are orders of magnitude better. Nonpolar analytes (steroids, alkynes) are ionized by rESI using an open‐tube secondary capillary and injecting electrolytically generated metal cations from the primary electrospray.